Responses to violence and human suffering in Christian hymnody: A study of responses to situations of violence in the work of four hymn writers - Tönsing, J. Gertrud (HTS teologiese studies, 2019)
This article looks at violence and the response to violent situations from the perspective of Christian hymnody. It examines where the content of hymns reflects experiences of violence and the hymn writers’ response to this. The work of four hymn writers is studied: two German traditional hymn writers and two contemporary English hymn writers. In each case, the article examines how they describe the violent situation, how they deal with the issue of human guilt, and what their response is. The article points out that often, hymns that deal with difficult issues do not become easily accepted in the congregational repertoire. However, as can be seen in these four cases, sometimes hymn writers do manage to find the language that can ensure that a hymn or song becomes a deep-felt way for congregations to express their feelings and experiences. Important in this acceptance is whether the hymn finds an appropriate expression of hope beyond the pain.